PELAKSANAAN PENCATATAN BLOKIR HAK ATAS TANAH PADA BUKU TANAH OLEH BUKAN PEMEGANG HAK DI KANTOR PERTANAHAN KABUPATEN PASAMAN BARAT - Fitrawadi Nst, Erizka (UNES Law Review, 2021)
Block registration is an administrative action of the Head of the Land Office or an appointed official to determine the status quo (freezing) of temporary land rights against legal actions and legal events on the land. The owner of the certificate can be the aggrieved party when there is another party who requests the blocking of the certificate of land book while the requesting party does not have rights to the entire value of the land contained in the certificate for which the blocking is requested. At the Land Office of West Pasaman Regency, every year they receive requests for registration of blocking submitted by non-holders of land rights themselves.